THE STUDENTS’ PERCEPTION OF NOTETAKING TECHINIQUE IN READING SKILL AT UNISMUH MAKASSAR - Andi Magfira Fausia; Erwin Akib; Farisha Andi Baso (English Language Teaching Methodology, 2021)
This research aimed to find out The students’ perception of notetaking technique in reading skill at unismuh makassar the data werre conducted on november 2020 from 10 students of the fifth semester(e class).This use a descriptive qualitative research, the instrument was an interview. The interview was distributed to the students of fifth semester and it was taken on watsapp by voice note.The findings of this research showed that the result of the students’ perception of notetaking technique in reading skill, according to them they feel that notetaking technique is very usefull and it is very help them in learning and understand the subject. They express that notetaking is a good technique to appear in reading, cause with notetaking they just open their notes and they will read the notes and then they get the points from the text.